Development and internal validation of prognostic models to predict negative health outcomes in older patients with multimorbidity and polypharmacy in general practice - Müller, BS; Uhlmann, L; Ihle, P; Stock, C; von Buedingen, F; Beyer, M; Gerlach, FM; Perera, R; Valderas, JM; Glasziou, P; van den Akker, M; Muth, C (BMJ Publishing Group, 2020)
Background Polypharmacy interventions are resource-intensive and should be targeted to those at risk of negative health outcomes. Our aim was to develop and internally validate prognostic models to predict health-related quality of life (HRQoL) and the combined outcome of falls, hospitalisation, institutionalisation and nursing care needs, in older patients with multimorbidity and polypharmacy in general practices.